Understanding Purchase Intention Toward Augmented Reality Through The Perspective of The Technology Acceptance Model (TAM) Theory: A Study on Indonesian Gen Z - Nilna Muna; Melati Ayu Chasyim; Vithyacharan Retnasamy (Universitas Muria Kudus, 2025)
The purpose of this study is to examine how Augmented Reality Adoption (ARA) affects Purchase Intention (PI) among Indonesian Generation Z consumers, using Positive Attitude (PA) as a mediating variable. The study uses the Technology Acceptance Model (TAM) to explain how users' purchasing decisions are influenced by their perceptions of AR's usefulness, enjoyment, and interactivity. 270 respondents were given online questionnaires as part of a quantitative approach, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to evaluate the data. The findings demonstrate that PA has a considerable beneficial impact on PI and that ARA considerably affects both PA and PI. Furthermore, the association between ARA and PI is partially mediated by PA, suggesting that customers are more prepared to make purchases when they are feeling well. However, this study only includes respondents from Generation Z and excludes other mediating factors like perceived ease of use or consumer trust. To better understand AR-based consumer behavior, future research is advised to use a mixed-method approach and incorporate more variables.